Comparing Guidelines Concerning Construction of the S-N Curve within Limited Fatigue Life Range - Strzelecki Przemysław; Sempruch Janusz; Nowicki Krzysztof (Polish Maritime Research, 2015)
The article collates guidelines concerning experimental construction of the S-N fatigue curves within a limited fatigue life range. An attempt is made to compare these guidelines, based on experimental data recorded during rotating bending of a notched specimen made of 42CrMo4. The recorded differences in fatigue life values between the constructed curves reach the maximum of 12.2%. According to the above guidelines, the number of tests in particular test series varies from 6 to 28. Based on the performed analysis a conclusion was made that the increase in the number of tests leads to the increase of accuracy but, on the other hand, remarkably increases the time of the experiment and, consequently, its cost. In this context, it is the research worker who, taking into account a possible future use of the fatigue curve, should individually decide about its accuracy.